Consumer protection and dispute resolution in electronic contracts under Saudi law - Alshammary, Mohammed Abdullah (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
The technological revolution has a considerable effect on the aspect of contracts, which is leading to the emergence of a distinctive type called an electronic contract. The advent of this type of contract has led to the inception of certain problematic issues and several legal inquiries, among which is the issue of consumer protection through these international contracts. Among the problematic issues in the aspect of e-contract to which the consumer is a party is the determination of the competent courts to adjudicate disputes emanating from such contracts due to the weakness of a consumer, which necessitates special protection on him. The researcher has addressed these issues through the employment of deductive and comparative approaches and arrived at findings the most important of which are: There are many regulations in Saudi Arabia that addressed the problem of research, some of which have to do with e-contracts. Some of these regulations have also addressed the judicial procedures in Saudi Arabia, while some of them have dealt with arbitration and consumer protection. However, the Saudi legislation are still deficient in proffering an effective solution to the problem of determining the competent authority to hear cases of e-contracts to which the consumer is a party. There is no any current legislation in Saudi Arabia that is based on consumer protection nor is there any regulation governing electronic arbitration or mediation. Until present, the existing Saudi regulations are not sufficient to provide the consumer with adequate protection by determining the competent courts to adjudicate the disputes emanating from e-contracts to which he is a party. The research concluded into a number of recommendations, some of which are: The need for a consumer protection system which should include specific articles that determine the courts competent to adjudicate electronic disputes, give the consumer the right of choice to file his case to either the court in his residential area or that of the supplier, and prohibit any previous agreement to amend these rules in the jurisdiction. Regulations to govern electronic arbitration and mediation should also be enacted to not only allow all their procedures to be carried out using an electronic means but also to recognize all these procedures and their awards in the country.